Binocular rivalry in children on the autism spectrum. Issue 6 (16th March 2017) - Karaminis, Themelis; Lunghi, Claudia; Neil, Louise; Burr, David; Pellicano, Elizabeth
Abstract : When different images are presented to the eyes, the brain is faced with ambiguity, causing perceptual bistability: visual perception continuously alternates between the monocular images, a phenomenon called binocular rivalry. Many models of rivalry suggest that its temporal dynamics depend on mutual inhibition among neurons representing competing images. These models predict that rivalry should be different in autism, which has been proposed to present an atypical ratio of excitation and inhibition [the E/I imbalance hypothesis; Rubenstein & Merzenich, 2003]. In line with this prediction, some recent studies have provided evidence for atypical binocular rivalry dynamics in autistic adults. In this study, we examined if these findings generalize to autistic children. We developed a child‐friendly binocular rivalry paradigm, which included two types of stimuli, low‐ and high‐complexity, and compared rivalry dynamics in groups of autistic and age‐ and intellectual ability‐matched typical children. Unexpectedly, the two groups of children presented the same number of perceptual transitions and the same mean phase durations (times perceiving one of the two stimuli). Yet autistic children reported mixed percepts for a shorter proportion of time (a difference which was in the opposite direction to previous adult studies), while elevated autistic symptomatology was associated with shorter mixed perception periods. Rivalry in the two groups was affected similarly by stimulus type, and consistent with previous findings. Our results suggest that rivalry dynamics are differentially affected in adults and developing autistic children and could be accounted for by hierarchical models of binocular rivalry, including both inhibition and top‐down influences. Autism Res 2017 . ©2017 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research Autism Res 2017, 10: 1096–1106 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.